A1.35 Cryopreservation of human synovial tissue for biobanking purposes. (13th February 2015) - de Vries, M; Broeren, MGA; Bennink, MB; Plem, van Lent; van der Kraan, PM; Koenders, MI; van de Loo, FAJ
Abstract : Background and objectives: Human synovial tissue derived from joint surgery of osteoarthritis (OA) and rheumatoid arthritis (RA) patients is valuable material for studying fundamental research questions. However, due to improved treatment options for these patients less joint replacement surgery is needed and less articular material becomes available for research. Additionally, performing a standardised comparative experiment with fresh tissue is difficult as material is scarce and infrequently available. It would be ideal to store and collect all this valuable tissue for later use. Therefore, a cryopreservation method has to be developed and importantly, the cryopreserved tissue should perform as freshly obtained material. Materials and methods: We used bovine metacarpophalangeal synovial tissue as a model. The inner layers of the joint capsule are isolated and 3 mm biopsies are taken. Human synovial tissue is derived, with informed consent, from joint surgery and also frozen as 3 mm biopsies. Cryosections are made to prove synovial origin. Bovine and human biopsies are cryopreserved by slow freezing using several cryoprotectant (CPA) solutions (Cryostor CS2 and standard freezing medium containing 10% DMSO and 10% FCS). For slow freezing a Mr. Frosty is used assuring a temperature decrease of 1°C/min. Thawing has been performed at 37°C, followed by quick removal of the CPA solution. Viability has been determined by MTT, XTT and ATP assays. Results: Histologically, the bovine synovial lining layer is comparable to normal human synovium. No differences were observed between freshly isolated and frozen synovium by HE staining on paraffin sections. Culturing cryopreserved bovine synovial tissue showed viability of up to 70% as determined by MTT, XTT and ATP assays. Furthermore, the standard CPA solution gives slightly higher viability values compared to the Cryostor medium. A first test with human RA tissue showed even higher viability, almost reaching the fresh values, as determined by the XTT assay. When comparing the viability assays, negative control values (tissue frozen-thawed several times without CPA solution) are lowest for the ATP assay indicating this assay could be most optimal for determining viability. Conclusion: The first results of the viability testing after cryopreservation are promising. However, further testing, also with additional CPA solutions is required to validate the cryopreservation method. Next to general viability, preservation of the pathologic response is important. Experiments are ongoing to determine cytokine secretion after cryopreservation and this will shed some more light on the ability to preserve and biobank human synovial tissue.